Disonansi Hukum Penegakan Illegal Fishing di Zona Ekonomi Eksklusif Indonesia: Menuju Harmonisasi dengan Unclos 1982 - Moh. Hariyanto (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the harmonization of illegal fishing law enforcement policies in Indonesia's EEZ which is faced with tensions between national interests and the obligations of UNCLOS 1982. Using a juridical-normative method with a legislative and case approach, this study offers novelty on a systematic comparative analysis between Article 73 of UNCLOS and national sanctions policy. The results show that although national laws (Law No. 5/1983 and Law No. 31/2004) generally adopt the principles of UNCLOS, there is potential conflict over criminal sanctions and shipwreck policies. Harmonization is needed through strengthening regulations, coordination between institutions and the implementation of proportionality and due process.